ANALYSIS OF THE FORMULATION OF ZAKAT MAL TAX INCENTIVE POLICY AT THE DIRECTORATE GENERAL OF TAXES (DGT) - Sihombing, Mhd. Syukur; Asmuni, Asmuni; Harahap, Isnaini (Proceeding International Seminar of Islamic Studies, 2023)
Focus of this research is the formulation of taxation policies related to zakat mal as a tax incentives at the Directorate General of Taxes (DGT). The problems in this study include, first, how the zakat mal tax incentive policy is formulated and its problems. Second, there are certain perceptions that hinder the development of zakat mal tax incentive policies and thirdly there are considerations of costs and not benefits in its formulation. This type of research is normative research with a juridical and analytical approach. The results of the study concluded that there was an error in the formulation of the zakat mal tax incentive policy in the form of errors in the interpretation and grouping of zakat in Law 36 of 2008 Income Tax.